2010
DOI: 10.1111/j.1551-2916.2009.03524.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Microstructure and Fracture Toughness for Fibrous Materials for Diesel Particulate Filters

Abstract: The Mode I fracture toughness of fibrous SiC and mullite materials with 60%–70% porosity was determined under ambient conditions using the double‐torsion test method. The fracture toughness values obtained were 0.27 and 0.34 MPa·m1/2 for fibrous SiC and mullite, respectively. These fibrous ceramics exhibit greater fracture resistance than porous monolithic ceramics with similar levels of porosity. A higher degree of cross‐linking between the fibers led to further improvement in the fracture characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…At 62.7% porosity it has a fracture toughness of 0.34 MPa m 1/2 , as measured by the double torsion test. 34 ACM of comparable porosity has a fracture toughness of 0.54 MPa m 1/2 . It should be noted that the double torsion test produces fracture toughness values that are comparable to or slightly less than those determined by the single-edge notched beam test.…”
Section: Fracture Toughnessmentioning
confidence: 98%
“…At 62.7% porosity it has a fracture toughness of 0.34 MPa m 1/2 , as measured by the double torsion test. 34 ACM of comparable porosity has a fracture toughness of 0.54 MPa m 1/2 . It should be noted that the double torsion test produces fracture toughness values that are comparable to or slightly less than those determined by the single-edge notched beam test.…”
Section: Fracture Toughnessmentioning
confidence: 98%
“…The micro-cracks www.springer.com/journal/40145 J Adv Ceram 2018, 7(1): 5-16 9 are suggested to develop in cordierite during high temperature processing [22]. The level of porosity and the presence of micro-cracks can have impact on the mechanical properties of a cordierite [23,24].…”
Section: Physical Microstructural and Compositional Analyses Of Tmentioning
confidence: 99%
“…The level of porosity and the presence of these micro-cracks will influence the mechanical properties of cordierite. Gordon et al [23] reported the fracture toughness of monolithic cordierite to be about 0.242 MPa·m 1/2 , while the cordierite investigated by Shyam et al [24] was determined to have fracture toughness that varies between 0.38 and 0.45 MPa·m 1/2 , depending on notch orientation. Fracture toughness of cordierite has been reported to decrease with increase in porosity [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…performed double‐torsion testing of delicately harvested and elegant DPF‐cell‐wall specimens and estimated K Ic ~0.4‐0.5 MPa√m for porous cordierites. Gordon et al . estimated K Ic ~0.3 MPa√m for fibrous porous ceramics using the same test method.…”
Section: Introductionmentioning
confidence: 99%